Perlindungan Hukum terhadap Pemegang Saham Akibat Dilusi Saham pada Perseroan Tertutup - Al Ghany, Gathan Sulthon; Purwanto, Aldira Mara Ditta Caesar (Universitas Batanghari Jambi, 2024)
Legal protection for shareholders is an important issue in the context of share dilution in limited liability companies. Share dilution is an event that results in a decrease in the share ownership percentage of shareholders due to the issuance of new shares, with shareholders resulting in losses. This research was conducted using a normative juridical method with a statutory approach and a conceptual approach. This research was conducted to determine the obligations of closed limited companies towards shareholders, as well as the legal efforts that can be taken to obtain compensation or avoid share dilution for shareholders in closed companies. The results of this research show that additional capital causes share dilution, there are also changes to Return On Investment (ROI), and reduced Dividends Per Share (DPS) which causes losses for shareholders. Therefore, shareholders need legal protection, preventively through the board of commissioners by making an anti-dilution agreement for the company through the right to convert the right to purchase securities first to avoid share dilution as regulated in Article 43 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies and share repressive efforts to restore rights can be done by filing a lawsuit with the court as regulated in Article 61 of Law Number 40 of 2007 concerning Limited Liability Companies.